(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Personal brand is an effective marketing strategy, which promotes an influx of new clients and pricing surge. Creation of personal brand requires attentive strategy, developed by accounting for modern trends and innovations, since previous methods are quickly becoming outdated. This article tackles contemporary methods of personal brand creation, as well as evaluates influence and possible effects of their execution. Additionally special attention is paid towards problems arising during practical implementations of chosen strategy.